The amblyopic eye in subjects with anisometropia show increased saccadic latency in the delayed saccade task - Perdziak, Maciej; Witkowska, Dagmara; Gryncewicz, Wojciech; Przekoracka-Krawczyk, Anna; Ober, Jan (Frontiers in Integrative Neuroscience, 2014)
The term amblyopia is used to describe reduced visual function in one eye (or both eyes, though not so often) which cannot be fully improved by refractive correction and explained by the organic cause observed during regular eye examination. This developmental disorder of spatial vision affects about 2-5% of the population and is associated with abnormal visual experience (e.g. anisometropia, strabismus) during infancy or early childhood. Several studies have shown prolongation of saccadic latency time in amblyopic eye. In our opinion, study of saccadic latency in the context of central vision deficits assessment, should be based on central retina stimulation. For this reason, we proposed saccade delayed task. It requires inhibitory processing for maintaining fixation on the central target until it disappears – what constitutes the GO signal for saccade. The experiment consisted of 100 trials for each eye and was performed under two viewing conditions: monocular amblyopic / non-dominant eye and monocular dominant eye. We examined saccadic latency in 16 subjects (mean age 30±11 years) with anisometropic amblyopia (two subjects had also microtropia) and in 17 control subjects (mean age 28±8 years). Participants were instructed to look at central (fixation) target and when it disappears, to make the saccade toward the periphery (10 deg) as fast as possible, either left or the right target. The study results have proved the significant difference in saccadic latency between the amblyopic (mean 262±48 ms) and dominant (mean 237±45 ms) eye, in anisometropic group. In the control group, the saccadic latency for dominant (mean 226±32ms) and non-dominant (mean 230±29 ms) eye was not significantly different.By the use of LATER (Linear Approach to the Threshold with Ergodic Rate) decision model we interpret our findings as a decrease in accumulation of visual information acquired by means of central (affected) retina in subjects with anisometropic amblyopia.